Chemical ecology of the carrot fly, Psila rosae (F.): laboratory and field studies - Selby, Martin James (2004)
The carrot fly (Psila rosae F.) is an important pest of the cultivated carrot (Daucus carota) and other crop species in the family Apiaceae, since the larvae burrow into and feed on the developing roots. Current P. rosae control relies heavily upon the use of chemical insecticides, but these are inadequate. The aims of this study were to investigate the chemical ecology of P. rosae, particularly with regard to long range attractant and repellent semiochemicals suitable for incorporation into integrated pest management strategies; the incorporation of attractant host plant extracts, or semiochemical attractants, into the monitoring programme; and the development of an autodissemination trap for release of the pathogenic fungus Entomophthora schizophorae in the field for biological control. A number of techniques for the extraction of volatile semiochemicals from a wide range of host and non-host plant species, and P. rosae adults themselves, were employed and compared. Samples were analysed by gas chromatography (GC), and the biologically active components in these complex natural product extracts were located by coupled GC-electrophysiological techniques and identified by coupled GC-mass spectrometry (GC-MS). Responses to the electrophysiologically active compounds were compared using electroantennographic (EAG) analysis: one unusually high EAG response was observed to a toxic component in hemlock (Conium maculatum) leaf extract (y-coniceine). Of the forty-two EAG active components identified from common crop species and C. maculatum, eight had not previously been reported. A range of bioassay techniques (including four-arm star olfactometers, V-tube olfactometers, and oviposition bioassays) were employed to determine behavioural activity of the samples and identified compounds, but only the oviposition bioassay showed significant behavioural discrimination to y-coniceine. Further studies of longer range behavioural responses to volatile semiochemicals were performed in the field. Significant responses were seen to a known field attractant (combined trans-asarone and hexanal) and, for the first time, to a microwave assisted solvent extract of celery (Apium graveolens) leaf. A prototype autodissemination trap for E. schizophorae was produced and evaluated.